A 4D spacetime embedded in a 5D pseudo-Euclidean space describing interior of compact stars - Singh, Ksh Newton; Murad, Mohammad Hassan; Pant, Neeraj (© 2017, Springer New York LLC, 2018)
This article was published in the European Physical Journal A [ © 2017, SIF, Springer-Verlag Berlin Heidelberg. ] and the definite version is available at :http://doi.org/10.1140/epja/i2017-12210-1. The Journal's website is at: https://link.springer.com/article/10.1140%2Fepja%2Fi2017-12210-1